Mobile Phone Use in Education and Learning by Faculty Members of Technical-Engineering Groups: Concurrent Mixed Methods Design - Mohammadi, Mehdi; Sarvestani, Maryam Shafiei; Nouroozi, Sahar (Frontiers in Education, 2020)
The purpose of this study was to evaluate the Mobile Learning Acceptance among faculty members. The research methodology was a concurrent mixed methods design. Research Method in the quantitative part was descriptive-survey, and in the qualitative part a phenomenological approach was applied. In the quantitative part, the study population consisted of all female and male faculty members of technical-engineering groups at Shiraz University (N=147), where 87 participants were selected using stratified random sampling method. In the qualitative part, the participants included a small fraction of the same faculty members who had also participated in the quantitative part and were selected by purposive sampling approach with criteria technique. Research instruments consisted of a researcher-made scale of mobile learning acceptance. Upon verifying the validity and reliability of the scale, it was distributed among the subjects and the collected data were analyzed using SPSS 21 software. Qualitative data were collected from semi-structured interviews with faculty members who had an experience of mobile learning. The quantitative results indicated that in all aspects, except for Usefulness, the faculty members' acceptance of mobile learning was higher than average, and Usefulness was at a moderate level. In the qualitative part, after integrating and summarizing the data, a total of 17 basic themes and three organizing themes were extracted, including the benefits of mobile learning, the barriers and limitations of mobile learning, and the required infrastructure for effective implementation of mobile learning.